AN ANALYSIS OF CRO SELECTION PROCESS &RISK ASSESSMENT FOR ASTRAZENECA GENERIC DRUG DEVELOPMENT PROJECT IN CHINA - shetty, shraddha (2012)
The current challenging situation in the pharmaceutical industry has caused has many big pharmaceutical companies to move towards Generic drugs .As the markets in the western countries are nearing saturation emerging nations like India and China are attractive destinations for Pharma companies. The on-going healthcare reforms, rising economy, untapped rural market, improved infrastructure & population pool in China gives tremendous opportunities for pharmaceutical companies to grow their business. AstraZeneca, a leading global player in the Branded drugs recognizes the huge potential of the China Generic drugs Market. AstraZeneca aims to enter this market by producing high quality-low cost generic drugs to the China broad market, but since it is new to the field of generics it has chosen for the CRO to play a major role in the development and registration of these drugs. This research work explores the various aspects of the AstraZeneca Generic drug development project (self-development project) highlighting key areas like CRO selection process, project risk assessment & finally analysis of the AstraZeneca Generics drug Business model